İhracatta KDV iadesinin hesaplanması, raporlaması, denetimi ve örnek bir uygulama - Koç, Murat (My University, 2005)
Bu çalışmanın konusu İhracatta KDV İadesinin Hesaplanması, Raporlaması, Denetimi ve Örnek Bir Uygulamadır. Bu tezin hazırlanmasındaki amaçlardan birincisi, özellikle ihracatçı firmalar açısından çok büyük önem taşıyan, ihraç edilen malın bünyesine giren katma değer vergisinin indirim konusu yapılamaması ve indirilemeyen bu verginin ihracatçılara gerek mahsuben gerek nakden iade edilmesinde geçerli olan esasların neler olduğunun ortaya konulmasıdır. İkinci ve tezin asıl konusunu oluşturan amaç ise; iade işlemlerinin hangi esaslar dahilinde yapılacağı, hangi raporların düzenleneceği ve hangi belgelerin isteneceğidir. Bu sebeple, katma değer vergisi sisteminde bulunan istisnalar içinde önemli bir yer alan ihracata istisnası ve vergi iadesi hakkında açıklamalar yapılmıştır. Bu çalışma sekiz bölümden oluşmaktadır. Birinci bölümde; ihracat, ihracatçı ve ihracat türleri hakkında verilmektedir. Tezin ikinci bölümünde, katma değer vergisinde bulunan istisnalar ve ihracat istisnasına ilişkin bilgilere yer verilmiş ve detaylı olarak incelenmiştir. Tezin üçüncü bölümü; doğrudan mal ihracatında katma değer vergisi istisnasının nasıl olduğu, dördüncü bölümde hizmet ihracatında istisnanın nasıl olduğu, beşinci bölümde Türkiye'de ikamet etmeyenlere yapılan satışlarda istisna uygulamasının nasıl olduğu, altıncı bölümde ihraç kayıtlı teslimlerde istisnanın nasıl anlatılmaya çalışılmıştır. Yedinci bölümde; istisnaya konu olan verginin iade yer verilmiştir. Sekizinci bölümde ise örnek bir uygulamaya yer verilmiştir. Name and Surname: Murat KOÇ Field: Business Administration Programme: Accounting and Finance Supervisor: Assistant Prof. Dr. Fatma PAMUKÇU Degree Awarded and Date: Masters Degree - July 2005 Value Added Tax (VAT) Value Added Tax in Export,

THE ADUTING, THE REPORTING, THE COMPUTING OF THE VAT RETURN IN THE EXPORTING AREA AND A SAMPLE CASE The subject of this study is the The Auditing, The Reporting, The Computing Of The VAT Return In The Exporting Area And A Sample Case. One of the first aim of this thesis is not being in question of the value-added tax rebate which is deemed important for the firms and is included within the export of goods and with this aim to establish the grounds which are valid for the return of these taxes to the exporters both payment on account and in cash. The second and the virtual aim of this thesis is to determine the basis of the return processes, which reports are being prepared and which documents are being required. In this regard, the explanations have been made on the exportation exceptions which are important within the system of value added tax and tax rebate. This study comprises eight parts. In the first part one can find the general information on the export, exporter and the types of the export. In the second part the information on the exceptions of value added tax and exportation exceptions can be found and reviewed in details. One can find the information how the value added tax exceptions can be made in the direct of exportation of goods in the third part, how the exceptions can be made in the service exportation in the fourth part; how the exceptions' implementation can be applied to the sales of the Turkish nonresidents in the fifth part; how the exceptions can be explained in the delivery registered exports in the sixth part. It is mentioned to the return of the tax which is the subject of the exceptions in the seventh part, a sample case has been discussed in the eighth part.
Keywords: Dış ticaret; Gümrük tarifesi politikası; İhracat, Katma Değer Vergisi; Ticaret